Precursor-dependent heteroatom diversity in luminescent carbon quantum dots: their impact on physicochemical properties and free radical scavenging and antibacterial activities - Konwar, Pollab Mohan; Devi, Suman; Pandey, Satish Kumar; Devi, Khomdram Sandhyarani; Devi, Ayekpam Bimolini; Luwang, Meitram Niraj (Langmuir, 2025)
The fabrication of a multifunctional carbon quantum dot (CQD) from a novel carbon source is still continuing to be demanding and fascinating. The carbon precursor plays a crucial role in developing any particular properties of a CQD to suit a specific application. In this study, green (Rhus chinensis fruits) as well as chemical-based (ascorbic acid and urea) carbon sources were used for the fabrication of CQDs using a simple, cost-effective, and eco-friendly method. The various physicochemical and optical properties of R. chinensis fruit-derived CQD (CQD-RCF) and urea-assisted ascorbic acid-derived CQD (CQD-AAU) were thoroughly investigated by using multiple characterization techniques such as XRD, TEM, HR-TEM, Raman, XPS, FT-IR, UV-vis, PL, and zeta potential. The synthesized CQDs were screened for antioxidant properties by a DPPH assay and antibacterial activity by the agar tip-well method. Both of these synthesized CQDs exhibited a variety of dissimilarities regarding their heteroatom compositions and surface functional groups, which subsequently led to an enhanced DPPH radical scavenging efficacy of CQD-AAU and a declared antibacterial efficacy of CQD-RCF. Therefore, the outcome of this study shows that the physicochemical properties and functionalities of CQDs are influenced by the chemical composition of the precursor material.